Pencapaian Tujuan Perusahaan dengan Customer Relationship Management pada Industri Jasa Telekomunikasi - Adhi Nugroho Chandra; Angga Hardian Anugrah; Christianus Ambardi Setyoko (Bina Nusantara University, 2013)
Marketing strategies can include forms of chosen marketing communications and marketing mix strategy. A company should maintain its consumer loyalty in a long term to prevent its product being “lost” due to lack of after-sales service. Thus, a concept of customer relationship management appears to improve customer satisfaction. Furthermore, for the company, implementing a strong customer relationship management will support other business units so that the corporate goal to gain profit will be achieved, considering the function of CRM is part of marketing unit the as spearhead of the company. CRM development cannot beseparated from technology. Therefore the use of CRM combined with web-based technology will result in a line of the target of a company, especially a telecommunication company, to face competition.